Devolution of powers and utilisation of resource under panchayat raj system in Andaman and Nicobar islands - Biswas, S.K. (2010)
India's independence has created a hope that decentralised governance will be able to retrieve her past glory through introduction of Gandhian ideals of "Gram Swaraj" by creating a polity with maximum powers devolved to the local bodies. The introduction of new Panchayati Raj Institutions (PRIs) with the passage of the 73rd Constitutional Amendment (1993) has created roadmaps for this dream. It is hoped that the process of political and administrative decentralisation will enable the PRIs to become instruments of decision making with autonomy and administrative capacity, ability for proper planning, power and resources for effective implementgation of panchayat initiated development plans. But the existing situation shows a wide gap between the expected and the actual. - Reproduced.
Keywords: Panchayat - India - Andaman and Nicobar Islands; Panchayat